2017
DOI: 10.7567/jjap.56.110312
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy studies of the intermediate layers at the SiO2/GaN interface

Abstract: As the first step toward understanding the electrical properties of SiO2/GaN systems, the interface was characterized using high-resolution scanning transmission electron microscopy (STEM) and energy dispersive X-ray spectroscopy (EDS). An epitaxial crystalline intermediate layer with a thickness of ∼1.5 nm was observed at the SiO2/GaN interface. STEM-EDS analyses revealed that this intermediate layer contained gallium and oxygen and mostly comprised the ε-Ga2O3 phase. The ε-Ga2O3/GaN interface was atomically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…However, even this kind of oxide layer can consist of multiple crystalline forms with disordered phases and Ga-related defects 28,30) . Therefore, an uncontrolled surface oxide layer may be a source of disorder at the GaN surface and metal/GaN interfaces, although a "well-controlled" native oxide layer has been reported to reduce the interface state density at the insulator/GaN interface [31][32][33] . According to the disorder-induced gap state (DIGS) model 8) , the origin of Fermi level pinning at the surface and interfaces is the gap states induced by disorder in chemical bonding.…”
Section: Introductionmentioning
confidence: 99%
“…However, even this kind of oxide layer can consist of multiple crystalline forms with disordered phases and Ga-related defects 28,30) . Therefore, an uncontrolled surface oxide layer may be a source of disorder at the GaN surface and metal/GaN interfaces, although a "well-controlled" native oxide layer has been reported to reduce the interface state density at the insulator/GaN interface [31][32][33] . According to the disorder-induced gap state (DIGS) model 8) , the origin of Fermi level pinning at the surface and interfaces is the gap states induced by disorder in chemical bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of a Ga oxide layer at the SiO 2 /GaN interface layer has also been observed . After depositing the SiO 2 layer by PECVD with tetraethyl orthosilicate (TEOS) gas and O 2 plasma, a 1.5 nm‐thick Ga 2 O 3 phase formed at the SiO 2 /GaN interface . However, the SiO 2 /GaN interface remains insufficiently understood.…”
Section: Introductionmentioning
confidence: 98%
“…Conventionally, an oxide layer of Al 2 O 3 or SiO 2 is deposited on the GaN layer. The surface of the GaN layer is either unintentionally oxidized during this process or intentionally oxidized via thermal oxidation or plasma treatment . There is still controversy as to whether the GaO x layer formed at the interface between the oxide and GaN layers effectively reduces the interface defect. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to this fundamental scientific interest, precise control of the reaction at the atomic scale is required for constructing efficient MOS structures in electronic devices. Thus, the mechanism of O 2 adsorption is attracting considerable attention, and many experimental and theoretical studies have been reported. However, a number of issues remain concerning the mechanism of the dissociative adsorption of O 2 . The most widely used experimental methods for investigating surface reaction dynamics are the reactive molecule beam scattering technique and X-ray photoelectron spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%